2020
DOI: 10.11591/edulearn.v14i2.15084
|View full text |Cite
|
Sign up to set email alerts
|

Proposing a model of critical literacy program for fostering Indonesian EFL students’ critical thinking skills

Abstract: This study was intended to depict how Critical Literacy Pedagogy (CLP) principles were incorporated in EFL reading class in Indonesian secondary school and the students' Critical Thinking (CT) were fostered during learning process. This study was a classroom practice-based model of how the principles were transferred into the detailed teaching syntax in an Islamic senior high school in West Java Indonesia. As a case study elaborating how a phenomenon happened, this study explored teaching steps, teacher-studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This study suggests that teachers use the existing GBP to introduce critical pedagogy principles. Different from previous studies in critical pedagogy and language teaching that mainly focus on incorporating critical pedagogy (see Mambu, 2018;Yulianto, 2020;Kurniawati et al, 2020;Chandrasoma & Ananda, 2018), this current study successfully intersected the two teaching approaches of critical pedagogy and genre pedagogy. Hence, rather than composing a specific method of teaching critical pedagogy, this study embeds the paradigm in the more 'fixed method' of genre pedagogy.…”
Section: Back and Forwardmentioning
confidence: 91%
See 1 more Smart Citation
“…This study suggests that teachers use the existing GBP to introduce critical pedagogy principles. Different from previous studies in critical pedagogy and language teaching that mainly focus on incorporating critical pedagogy (see Mambu, 2018;Yulianto, 2020;Kurniawati et al, 2020;Chandrasoma & Ananda, 2018), this current study successfully intersected the two teaching approaches of critical pedagogy and genre pedagogy. Hence, rather than composing a specific method of teaching critical pedagogy, this study embeds the paradigm in the more 'fixed method' of genre pedagogy.…”
Section: Back and Forwardmentioning
confidence: 91%
“…When incorporating critical pedagogy in EFL classes, published studies that examined critical pedagogy and EFL teaching are mostly limited to research about teachers' reflections and teachers' difficulties (Mambu, 2018;Chandrasoma & Ananda, 2018). Regarding skills to improve, research in this field has proven that critical pedagogy improves reading skills (Kurniawati et al, 2020) and speaking skills (Chandrasoma & Ananda, 2018). Despite the contribution, none of these studies focused on developing students' writing skills.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Kurniawati et al (2020) implemented a critical literacy initiative for Indonesian EFL students at Gunung Djati Bandung University in Sunan. Utilizing Critical Literacy Pedagogy (CLP) with 29 eleventh-grade science and social studies students led to notable advancements in recog-nizing the author's intent and the logical contextualization of texts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Saputra, Joyoatmojo, Wardani and Sangka (2018), who focused their study on improving students' critical thinking through a jigsaw problem-based collaborative learning model, found that their model was effective. Similarly, Kurniawati, Sugaryamah, and Hasanah (2020), who focused their study on incorporating critical literacy pedagogy (CLP), found that CLP can enhance students' engagement with critical thinking.…”
Section: Introductionmentioning
confidence: 99%